Analysis of Techniques and Strategies in Learning - Didik Himmawan; Ifan Zamborano (El-Ma'wa: Journal of Arabic, Translation and Linguistic, 2025)
Learning techniques are the way teachers deliver teaching materials that have been prepared (in methods), based on the approach adopted. The techniques used by teachers depend on the teacher's ability to find ideas or strategies so that the teaching and learning process can run smoothly and be successful. The method used in this paper is a qualitative method with a literature study approach from relevant sources through books and articles, conclusions are conveyed narratively relating to relevant discussion themes. The conclusion of this paper is that in determining this learning technique, teachers need to consider the class situation, environment, student conditions, student characteristics, and other conditions. Thus, the learning techniques used by teachers in delivering can be well received. The same method can be used with different learning techniques, depending on various factors in the classroom.